THE IMPLEMENTATION OF WASHING CYCLE IN LAUNDRY SECTION AT HOTEL PANGERAN PEKANBARU - Dandi Alfarouk Damirano; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The City of Pekanbaru provides many accommodation places with fairly good facilities, with a strategic location and abundant varities. Many types of accommodation have developed in Pekanbaru City, one of which is a five-star hotel, especially the Hotel Pangeran Pekanbaru which is a four-star hotel. This study aims to determine the implementation of the washing cycle in the laundry section at the Hotel Pangeran Pekanbaru. This study relates the application of the washing cycle to the elements of Flush, Break, Suds, Carryover Suds, Bleach, Rinse, and Extract. This study uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. The sources of informants in this study were the Manager, Supervisor, and Laundry Attendant at the Laundry Section of the Hotel Pangeran Pekanbaru. In this study, the data collection techniques used were interviews, observation and documentation. The results of this study reveal that the implementation of services has been carried out based on the relevant Washing Cycle by paying attention to the elements of Flush, Break, Suds, Carryover Suds, Bleach, Rinse, and Extract. Keywords: Application, Cycle, Washing, Hotel Pangeran Pekanbaru.